Integrating Industrial Hygiene into Public Health Programs: Community-Level Approaches to Hazard Assessment and Control - Holt, Kimberly Long (Indonesian Journal of Advanced Research, 2025)
This research examines integrating industrial hygiene principles into public health programs to address community environmental health risks. Using a mixed-methods approach combining literature review and case study analysis, we evaluated industrial hygiene interventions in schools, healthcare facilities, and informal settlements. Three case studies demonstrated significant health improvements: 15% reduction in asthma-related school absenteeism, 45% decrease in healthcare worker respiratory symptoms, and 35% reduction in childhood respiratory infections in informal settlements. Results show industrial hygiene methods effectively reduce environmental exposures when adapted for community settings. The study contributes novel frameworks for expanding occupational hygiene beyond workplace applications, offering systematic approaches for community hazard assessment and control. Integration requires addressing resource limitations, building technical capacity, and ensuring community engagement for sustainable implementation.